The use of controversial public issues with video and macromedia flash player media in civic education learning - Hendra Hermawan; Samsuri Samsuri; Diah Putri Kurniawati; Vinni Sofyaningsih; Danang Prasetyo (Research and Social Study Institute, 2018)
The study aimed to find out the effect of controversial public issue learning models with video and Macromedia flash player media on students’ critical thinking skills in Civic Education subjects at SMA Negeri 1 Rancah. The particular research was a quasi-experimental research using pretest, posttest control group design. Data analysis techniques used independent t-test and one-way ANOVA test. The results showed that critical thinking skills on students taught using Controversial Public Issues model with video media had a significant effect on the critical thinking ability. This finding might be seen from the one-way ANOVA test results that the Fcount> Ftable (61.146> 3.13) or the p-value is lower than 0.05 (p = 0.000 <0.05) and the gain score. The experimental class 1 obtained a gain score of 0.49 in the category of